Kelayakan dan Strategi Pengembangan Usaha Beras Cimanuk Melalui Peningkatan Mutu Oleh PD Jaya Saputra Kecamatan Cimanuk Kabupaten Pandeglang Provinsi Banten - . Nasir; Mochamad Hasjim Bintoro; Wilson Halomoan Limbong (Institut Pertanian Bogor, 2012)
PD Jaya Saputra as a Small Medium Enterprise (SME), which produces Cimanuk rice, wants its product to become Pandeglang’s pride icon. Cimanuk rice has a good quality, so it can penetrate not only the national but also the international market (export). The objective of this study are (1) Identify and evaluate the condition of SMEs PD Jaya Saputra, (2)Analyze the feasibility of business development through quality improvement, and (3) Prepare alternative strategies appropriate for their business development through quality improvement.The data needed for this study originated from the primary and secondary data. The data analysis was performed through adescriptive methods, namely SWOT, QSPM, and feasibility analysis through assessment criteria the PBP, Net B/C, BEP, NPV, and IRR. IFE matrix resulted in a score of 2.688, EFE matrix of 2.758, and the IE matrix, all of which are in quadrant V, namely growth/stabilization quadrant, which means that the firm must conduct strategies for market penetration and development. The recommended strategies are applying rice production technology to obtain quality, improving and maintaining quality in accordance to the rice grades and quality regulation to maintain consumer’s loyalty, improving quality of human resources in production and marketing section through informal channels. The results of the eligibility criteria analysis showed the BEP 84.866, PBP 32 months, Net B/C 1.044, a positive NPV 765.395, and IRR 17%. The quality improvement can be done through improvement of management and human resources, cultivation, harvesting and post-harvesting, including machine repair and proper packaging